Ambient air pollution, adipokines, and glucose homeostasis: The Framingham Heart Study. (February 2018) - Li, Wenyuan; Dorans, Kirsten S.; Wilker, Elissa H.; Rice, Mary B.; Kloog, Itai; Schwartz, Joel D.; Koutrakis, Petros; Coull, Brent A.; Gold, Diane R.; Meigs, James B.; Fox, Caroline S.; Mittleman, Murray A.
Abstract: Objective: To examine associations of proximity to major roadways, sustained exposure to fine particulate matter (PM2.5 ), and acute exposure to ambient air pollutants with adipokines and measures of glucose homeostasis among participants living in the northeastern United States. Methods: We included 5958 participants from the Framingham Offspring cohort examination cycle 7 (1998–2001) and 8 (2005–2008) and Third Generation cohort examination cycle 1 (2002–2005) and 2 (2008–2011), who did not have type 2 diabetes at the time of examination visit. We calculated 2003 annual average PM2.5 at participants' home address, residential distance to the nearest major roadway, and daily PM2.5, black carbon (BC), sulfate, nitrogen oxides (NOx ), and ozone concentrations. We used linear mixed effects models for fasting glucose, insulin, and homeostasis model assessment of insulin resistance (HOMA-IR) which were measured up to twice, and used linear regression models for adiponectin, resistin, leptin, and hemoglobin A1c (HbA1c) which were measured only once, adjusting for demographics, socioeconomic position, lifestyle, time, and seasonality. Results: The mean age was 51 years and 55% were women. Participants who lived 64 m (25th percentile) from a major roadway had 0.28% (95% CI: 0.05%, 0.51%) higher fasting plasma glucose than participants who lived 413 m (75th percentile) away, and the association appeared to be driven by participants who lived within 50 m from a major roadway. Higher exposures to 3- to 7-day moving averages of BC and NOx were associated with higher glucose whereas the associations for ozone were negative. The associations otherwise were generally null and did not differ by median age, sex, educational attainment, obesity status, or prediabetes status. Conclusions: Living closer to a major roadway or acute exposure to traffic-related air pollutants were associated with dysregulated glucose homeostasis but not with adipokines among participants from the Framingham Offspring and Third Generation cohorts. Highlights: Living closer to a major roadway was associated with higher fasting glucose. Annual average PM2.5 was not associated with measures of glucose homeostasis. Short-term exposure to BC and NOx were positively associated with fasting glucose. Short-term exposure to O3 was negatively associated with fasting glucose.